Health Education about Dental Health of School Children at SDN 7 Sukamenteri, Garut Kota District - Iwan Shalahuddin; Udin Rosidin; Umar Sumarna; Nina Sumarni; Ahmad Yamin; Mamat Lukman (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Dental health problems can have a negative impact and affect the quality of life for children, dental health problems such as cavities and dental caries will cause pain and discomfort. This will also interfere with children's activities at school, where children will experience a decrease in learning abilities, children with dental pain will not do their homework, and it is difficult to answer questions as well as children who are not bothered by dental health problems. Dental and Oral Health, Mouth is formed by 2 jaws, namely the upper and lower jaws. In this jaw there are teeth and gums. The teeth and mouth themselves function to chew, speak, and give a harmonious shape to the face. The purpose of education is to provide and improve students' understanding of the importance of preventing dental health problems and to identify the importance of early detection to avoid dental disease. The method used is the lecture method, question and answer, discussion and demonstration. The results of the health counseling activities were approximately 151 students. The counseling participants looked enthusiastic when the material was given. Participants participated in the counseling happily because the counseling was carried out in a fun way. The counseling activity was conducive because the participants paid attention to the material presented well. This is evidenced by the number of participants who are interested in answering questions during the question and answer session. Participants participated in the counseling happily because the counseling was carried out with a pleasant face-to-face method. The counseling activity was conducive because the participants paid attention to the material presented well about personal hygiene and dental and oral hygiene.